Separation of methionine and arginine onto calix[4]arene grafted Merrifield resin - Reza Zadmard; Fahimeh Hokmabadi; Mohammad Reza Jalali (Results in Chemistry, 2023)
Based on host–guest complexation and a utilizing a functionalized Merrifield resin, a practical method was developed to separate methionine and arginine mixtures. To obtain the resin, a new derivative of calix[4]arene was immobilized on Merrifield resin. The resin was recyclable and it was used for several times for rapid and convenient separation of amino acids from the mixtures mentioned above.